2017
DOI: 10.1080/17429145.2017.1397206
|View full text |Cite
|
Sign up to set email alerts
|

Leaf gas exchange, physiological growth, yield and biochemical properties of groundnut as influenced by boron in soilless culture

Abstract: Crops specific proper concentration of micronutrient application is necessary to improve the yield and quality of crops. Therefore, an experiment was conducted to identify the optimum dose of boron for groundnut plant. Six level of boron (B) application, B 0 (0 ppm), B 1 (0.5 ppm), B 2 (1 ppm), B 3 (2 ppm), B 4 (4 ppm) and B 5 (8 ppm) were evaluated. Photosynthetic rate, transpiration and stomatal conductance were increased for boron application but leaf vapor pressure deficit decreased. Physiological growth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…This might be due to that full strength of Rhaman and Inden contained all plant nutrient elements in proper proportion which helped the plants developing a larger size and shape of fruits. The plants required optimum nutrient combination for proper growth and better yield stated by Quamruzzaman et al (2017). The results of the present study were consisted with the findings of Nandapuri et al (1973) and Ahmed et al (1988).…”
Section: Number Of Flowers Per Clustersupporting
confidence: 87%
“…This might be due to that full strength of Rhaman and Inden contained all plant nutrient elements in proper proportion which helped the plants developing a larger size and shape of fruits. The plants required optimum nutrient combination for proper growth and better yield stated by Quamruzzaman et al (2017). The results of the present study were consisted with the findings of Nandapuri et al (1973) and Ahmed et al (1988).…”
Section: Number Of Flowers Per Clustersupporting
confidence: 87%
“…On the other hand, full strength of Rahman and Inden (2012) solution (N 1 treatment) provided optimum and proper nutrient combination for high-value crops. Quamruzzaman et al (2017) suggested that maximum stomatal pores in the epidermal layers of leaves were opened because of proper supply of nutrient solution. The result suggesting that the increased E was associated with the increased P N and g s agreed with the finding of Lu et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…The yield contributing char-acters performed better in N 1 nutrient solution. This might be due to an adequate supply of nutrient combination provided by treatment N 1 , resulting in the maximum reproductive growth (Quamruzzaman et al, 2017) because the plants required optimum nutrient combination for proper growth and better yield. When all the plant nutrients with the growth promoters and the regulators were supplied, the metabolic function of the plants would progress in the right direction and rate, whereas the yield and yield contributing characters increased gradually .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations